2020
DOI: 10.15585/mmwr.mm6929e2
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Community Seroprevalence of SARS-CoV-2 Antibodies — Two Georgia Counties, April 28–May 3, 2020

Abstract: this report was posted as an MMWR Early Release on the MMWR website (https://www.cdc.gov/mmwr).Transmission of SARS-CoV-2, the virus that causes coronavirus disease 2019 (COVID-19), is ongoing in many communities throughout the United States. Although case-based and syndromic surveillance are critical for monitoring the pandemic, these systems rely on persons obtaining testing or reporting a COVID-19-like illness. Using serologic tests to detect the presence of SARS-CoV-2 antibodies is an adjunctive strategy t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
126
6

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(143 citation statements)
references
References 6 publications
11
126
6
Order By: Relevance
“…A total of 18 studies were contact-tracing studies (CTSs), 7,10,12,16-31 with 3 based in schools, [29][30][31] and 14 studies were population screening studies. 7, [32][33][34][35][36][37][38][39][40][41][42][43][44][45] Two were high quality, 33,35 22 were medium quality, 10,12,16,21,22,[24][25][26][27][29][30][31][32]34,36,38,[40][41][42][43][44][45] 7 were low quality, [17][18][19][20]23,28,39 and 1 was uncertain quality. 7,37…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 18 studies were contact-tracing studies (CTSs), 7,10,12,16-31 with 3 based in schools, [29][30][31] and 14 studies were population screening studies. 7, [32][33][34][35][36][37][38][39][40][41][42][43][44][45] Two were high quality, 33,35 22 were medium quality, 10,12,16,21,22,[24][25][26][27][29][30][31][32]34,36,38,[40][41][42][43][44][45] 7 were low quality, [17][18][19][20]23,28,39 and 1 was uncertain quality. 7,37…”
Section: Resultsmentioning
confidence: 99%
“…Data from prevalence studies for children and adolescents compared with adults are shown in Figure 4. 7, [32][33][34][35][36][38][39][40][41][42][43][44][45] We did not undertake a meta-analysis of population screening studies given the important differences in the populations, epidemic time points, and methodologies involved.…”
Section: Population Screening Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the overall seroprevalence was 8.7% with a wide range among studies from 0% to 45.3%. Population-based and community-based studies in USA showed a great variability in seroprevalence of SARS-CoV-2 antibodies from 1.1% to 14.4% [63][64][65][66][67]. Similar studies in Europe [68][69][70] and China [71] found very different seroprevalence in general population ranging from 0.23% to 10.9%.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is essential that we carefully study and document the neutralizing antibody responses in recovered individuals. SARS-CoV-2 antibody testing is critical to understanding who has been infected and to provide a picture of seroprevalence in a community [4][5][6][7][8][9] . However, while these tests are important and provide a relative antibody titer, they are seen more as a "yes or no" type of answer to whether an individual has been infected.…”
Section: Introductionmentioning
confidence: 99%